Corporate Governance Dan Profitabilitas: Pengaruhnya Terhadap Corporate Social Responsibility Perusahaan Yang Listing Di Bei - Ninda Eka Agustina; Moh. Syadeli (Conference In Business, Accounting, And Management (CBAM), 2012)
Corporate Governance is a set of systems that regulate and control the enterprise in creating added value for stakeholders and stockholders who provide long-term benefit. Companies with high profitability will present information corporate social responsibility (CSR) more. CSR is used to bridge the companyâ€™s interests with the interests of stakeholders that the companyâ€™s activities in dealing with environmental pollution as well as the obligations of the company on the issue of financial accountability through reporting company and the information needs to be known by stakeholders. The purpose of this study was to analyze the effect of corporate governance (institutional ownership, board of directors) and the profitability of the CSR with firm size as control variables. The sample was selected using purposive sampling method under consideration (judgment sampling) to obtain samples of food and beverages 39 companies listed in the Indonesia Stock Exchange in 2008-2010. Methods of analysis using multiple regression analysis with the results of (1) Institutional Ownership, commissioners and profitability significantly influence the CSR, (2a) Institutional Ownership no significant effect on CSR, (2b) The Board of Commissioners significant effect on CSR, (3) significant Profitability towards CSR.Keywords: Corporate Governance, Institutional Ownership, Board of Commissions,Â Corporate Social Responsibility.